Thermal properties of fluoride glasses and their gel precursors - Melnikov, P.; Rolim, R.; Delben, A.; Delben, JR; Souza, A. C.; Job, A. E. (Kluwer Academic Publ, 2004)
Xerogels were prepared from zirconium, barium, aluminum, lanthanum and lithium acetates, corresponding to a Li containing ZBLA composition. The study of their thermal properties (DSC, TG/DTG, FT-IR) showed that they might be used as chemically stable precursors in the preparation of fluoride glasses. Hydrofluoric acid in solution was chosen as a mild fluorinating agent. This newly proposed technique of fluorinating allowed to obtain high quality ZBLALi glass which presents the advantage of higher thermal stability and homogeneity in comparison with the glass obtained using individual commercial fluorides.
Keywords: fluoride glasses; glass precursors; xerogels